Microwave‐assisted Synthesis, Characterization, and Density Functional Theory Study of Biologically Active Ferrocenyl Bis‐pyrazoline and Bis‐pyrimidine as Organometallic Macromolecules. (7th December 2018) - Khan, Salman A.; Asiri, Abdullah M.; Zayed, Mohie E. M.; Parveen, Humaira; Aqlan, Faisal M. S.; Sharma, Kamlesh
Abstract : Organometallic macromolecules such as ferrocenyl bis‐pyrazoline (2, 3 ) and bis‐pyrimidine (4, 5 ) derivatives were synthesized by reacting ferrocenyl bis‐chalcone 1 with thiosemicarbazide/phenylhydrazine/guanidine hydrochloride/thiourea, respectively, under microwave irradiation. Ferrocenyl bis‐chalcone 1 was synthesized by reacting acetyl ferrocene with terephthalaldehyde. Synthesized compounds were characterized by using IR, 1 H NMR, 13 C NMR, EI‐MS, and elemental analysis. In vitro antibacterial activity against two Gram‐negative and two Gram‐positive bacteria was determined by the disc diffusion assay. Moreover, minimum inhibition concentrations were also measured with reference to chloramphenicol. Thioamide functionally containing ferrocenyl bis‐pyrazoline derivative 2 shows the best antibacterial activity on Escherichia coli and Salmonella typhimurium, among all tested compounds including the reference drug chloramphenicol. The structure–activity relationship is also developed by using computational calculations with density functional theory (DFT)/B3LYP method. Abstract :